2001
DOI: 10.1080/00288306.2001.9514956
|View full text |Cite
|
Sign up to set email alerts
|

Terrane affiliation and terrane boundaries of Mesozoic accretionary complexes, northeastern North Island, New Zealand: Some implications from recycled elastics

Abstract: In the late Mesozoic Waioeka petrofacies in northeastern North Island, New Zealand, sandstone pebbles differ significantly in petrography from their enclosing sandy conglomerate matrix, and yield contrasting provenance signatures. The compositional contrast demonstrates the extrabasinal origin of most of the analysed clasts. Differences in clast provenance have been used to review boundaries and the terrane affiliation to the neighbouring Torlesse and Waipapa composite terranes.A previously postulated Cretaceo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Torlesse nomenclature (both lithostratigraphic and tectonostratigraphic) has been applied to them (Speden 1976;Mortimer 1995a). Recent research in the Whakatane-East Cape area (Mortimer 1995a;Kear 2000;Leverenz & Ballance 2001) has confirmed that Triassic Rakaia and Jurassic-Cretaceous Pahau Terranes form the core of the central North Island ranges (Fig. 1); they are composed of quartzofeldspathic greywackes (e.g., Fig.…”
Section: Whakatane-east Cape Areamentioning
confidence: 99%
See 4 more Smart Citations
“…Torlesse nomenclature (both lithostratigraphic and tectonostratigraphic) has been applied to them (Speden 1976;Mortimer 1995a). Recent research in the Whakatane-East Cape area (Mortimer 1995a;Kear 2000;Leverenz & Ballance 2001) has confirmed that Triassic Rakaia and Jurassic-Cretaceous Pahau Terranes form the core of the central North Island ranges (Fig. 1); they are composed of quartzofeldspathic greywackes (e.g., Fig.…”
Section: Whakatane-east Cape Areamentioning
confidence: 99%
“…5B). In most areas, the Waipa and Pahau rocks are separated from each other by melange, although at Hendersons Quarry quartzose Rakaia or Pahau clasts may be present in Waipa conglomerates (Leverenz & Ballance 2001), and depositional relationships may yet be revealed elsewhere. We also exclude from Waipa Supergroup the younger, more quartz-rich sandstones of the Omaio petrofacies (East Cape; Mortimer 1995a) and Tokatea Hill Formation (Coromandel; Skinner 1972).…”
Section: An Improvement In North Island Basement Nomenclature?mentioning
confidence: 99%
See 3 more Smart Citations